DO WOMEN IN RURAL AREAS STILL PREFER HOMEBIRTH WITH TRADITIONAL BIRTH ATTENDANTS? A QUALITATIVE STUDY OF WOMEN IN RURAL AREA OF KUTAI KERTANEGARA EAST KALIMANTAN - Nurrachmawati, Annisa; Hakimi, Moh.; Utarini, Adi (YCAB Publisher & IAKMI SULTRA, 2018)
Background: There continues to be a gap between facility-based delivery and homebirth. This condition is influenced by various social and cultural factors, which in rural areas could affect childbirth in health facilities.Objective: This study aimed to explore whether there has been a shift from homebirth to facility-based delivery and what factors are associated with the phenomenon.Method: A qualitative longitudinal research with ethnographic study design was conducted in the working area of Muara Kaman Health Center in Kutai Kertanegara District, East Kalimantan. The data were collected using in-depth interviews of 17 pregnant women as informants who were followed from the first or second trimester of pregnancy until delivery, and interviews with four midwives. Data were analyzed with thematic analysis.Results: Nine of the 17 women gave birth at the health facility, while there were still three who had homebirth assisted by traditional birth attendants. The number of women who performed deliveries at health facilities was increased from five in the previous pregnancy to nine in the current pregnancy during study. Women's autonomy and risk awareness were considered as enablers for delivery at health facilities, while perception of homebirth as appropriate for normal labor, unnecessary planning of place and birth attendants, and less optimum partnership between midwife and traditional birth attendants hindered facility-based delivery.Conclusion: Our findings suggest that the shift from homebirth to facility-based delivery has been slow. Efforts to minimize the barriers and improve supportive environment for women to deliver at health facilities should be strengthened.